Integrasi Model Pembelajaran Inkuiri Berbasis Kearifan Lokal dalam Meningkatkan Minat Belajar Siswa Sekolah Dasar - Farida Yuliana; Sekar Purbarini Kawuryan; Fery Muhammad Firdaus (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Learning interest is an important factor in determining the success of learning, especially at the elementary school level. This study aims to examine the effect of inquiry learning model integrated with local wisdom values on students' interest in learning. The method used was quasiexperiment with nonequivalent control group design. The research subjects consisted of fourth grade students from two elementary schools in Yogyakarta. The experimental group received treatment in the form of inquiry learning integrated with local cultural values of Yogyakarta, while the control group followed conventional learning. Data were collected through a validated learning interest questionnaire with high reliability (α = 0.842). The t-test results showed a significant difference between the experimental and control groups in terms of students' interest in learning (p < 0.001). This finding indicates that the integration of local wisdom in the inquiry model is effective in increasing students' attention, curiosity, and engagement in learning. The conclusion of this study confirms that the local wisdom-based inquiry learning model contributes positively to strengthening students' interest in learning, and is worth developing as a contextual and culturally relevant pedagogical approach.